Engaging the Professional Needs of Academics with Visual Impairments in a Post- COVID-19 Pandemic Higher Education System – The Case of Cameroon - Nyugap, Charly Ringnyu; Ngwa, Emmanuel Shu (Journal of Innovation in Education and Social Research, 2024)
The study examined the needs of Academics with Visual Impairments (AVI) in a post-COVID-19 pandemic Cameroon Higher Education (HE) system, for inclusive and equitable policy recommendations. It specifically focused was on: the challenges of AVI in responding to innovative options to teaching-learning, research and related functions adopted during and post-covid-19 pandemic eras; adaptation strategies employed by AVI during and after the pandemic, and the professional needs of AVI towards aligning with post-pandemic changes and adjustment to teaching-learning activities within the Cameroon HE system. The study was theoretically underpinned by the inclusive lens model by UNESCO (2009). Being a post-positivist - qualitative study, the researchers employed the exploratory research design, making a purposive use of six (6) AVI and four (4) administrators from HE institutions in Cameroon. With the use of a focus group discussion, focus group discussion guide, and an interview, the researcher explored the views of the AVI pertaining to the issues under examination. The findings revealed that; challenges of AVI in responding to teaching innovations during the period under consideration included; limited knowledge in the use of adapted teaching-learning technologies, insufficient financial resources to acquire adapted technologies for online teaching, insufficient and exclusive nature of staff training programs during COVID, absence of inclusive teaching learning technologies, and the negative attitudes and non-collaborative nature of some sighted staff in the execution of teaching-learning tasks. Their major adaptation strategies included the acquisition of adapted and assistive ICT devices, self-sponsored training on basic adapted ICT skills and self-sponsored recruitment of sighted aid volunteers to provided sighted assistance in lesson preparation and related duties. Professional needs of AVI for alignment with post-pandemic adjustments and innovations include among others; intense training on adapted e-learning for AVI and students with visual impairment (SVI), advanced training on the use of adapted ICT tools, provision of adapted teaching-learning ICT devices and materials for university libraries, digitalization of campus services to aid the mobility and interaction of AVI and SVI, training of institutional staff for attitudes change, and State or institution sponsored employment of sighted aids attached to all academic staff with visual impairment. The underlying recommendation was on the need for strict enforcement of the laudable existing national and international extant legislations and policies geared towards protecting and upholding the rights and welfare of persons with disabilities not only within educational and professional circles but across every sector of national life in Cameroon.